2024
DOI: 10.7759/cureus.52111
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Tranexamic Acid in Trauma Patients: A Systematic Review

Kenneth Meza Monge,
Sabrina S Domene,
Diana L Diaz Mendoza
et al.

Abstract: Tranexamic acid (TXA), a fibrinolytic agent, effectively inhibits plasminogen activation, thereby reducing fibrinolysis and hemorrhage. This study focused on its application in trauma patients undergoing emergency surgery, a critical area due to trauma's significant role in mortality. Our investigation involved a meticulous screening of randomized controlled trials from databases including Scopus, PubMed, Web of Science, and Cochrane. The findings indicate that TXA intervention is promising in enhancing outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Tranexamic acid binds a lysine receptor in plasmin and inhibits fibrinolysis. A recent systematic review demonstrated how the early management of tranexamic acid has been shown to have positive outcomes in gastrointestinal bleeding and traumatic events; it reduces continued gastrointestinal bleeding and urgent endoscopic intervention but has not shown improvement in all causes of mortality [44,57,58].…”
Section: Treatment Strategies For Bleeding Esophageal Varicesmentioning
confidence: 99%
“…Tranexamic acid binds a lysine receptor in plasmin and inhibits fibrinolysis. A recent systematic review demonstrated how the early management of tranexamic acid has been shown to have positive outcomes in gastrointestinal bleeding and traumatic events; it reduces continued gastrointestinal bleeding and urgent endoscopic intervention but has not shown improvement in all causes of mortality [44,57,58].…”
Section: Treatment Strategies For Bleeding Esophageal Varicesmentioning
confidence: 99%